Internal and external communication patterns at ora aji islamic boarding school yogyakarta - Qiyadah Robbaniyah; Roidah Lina; Mohieddin Masoud (At Turots: Jurnal Pendidikan Islam, 2025)
Inclusive and rehabilitative Islamic boarding schools such as the Ora Aji Islamic Boarding School face complex communication challenges amid the diversity of student backgrounds. This study aims to describe internal and external communication patterns, strategies, and communication barriers that occur in the pesantren environment. Using a descriptive qualitative approach, data was obtained through interviews, observations, and document analysis. The results showed that communication was arranged informally through the student assistance division and facilitated by media such as WhatsApp and HT. Communication strategies are carried out through a personal approach, regular meetings, and social activities with the community. The main obstacle lies in the background of the students and the limited resources of the management. The conclusion of this study emphasizes the importance of an adaptive communication system based on Islamic values and a personal approach in supporting the success of education and rehabilitation programs in inclusive Islamic boarding schools.